2023
DOI: 10.3390/antiox12091744
|View full text |Cite
|
Sign up to set email alerts
|

Gossypetin Is a Novel Modulator of Inflammatory Cytokine Production and a Suppressor of Osteosarcoma Cell Growth

Carina Proença,
Ana Teresa Rufino,
Isabela Santos
et al.

Abstract: Osteosarcoma (OS) is a common childhood sarcoma, and its treatment is hindered by adverse effects, chemoresistance, and recurrence. Interleukin (IL)-6 production by tumors plays a significant role in inflammation, carcinogenesis, and metastasis. This study aimed to investigate the antiproliferative potential of luteolin derivatives in OS and to evaluate interleukin production. MG-63, Saos-2, HOS, and 143B human OS cell lines were incubated with luteolin and eight derivatives containing hydroxy, chlorine, or al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Cadmium chloride (CdCl 2, 133 µg/ml) and methyl methanesulfonate (MMS, 3.67 mg/ml) were dissolved directly in 1 % DMSO in PBS. The concentrations to use were based on previous experiments in vitro and in ovo [5] , [6] , [7] . All solutions were freshly prepared before inoculation.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Cadmium chloride (CdCl 2, 133 µg/ml) and methyl methanesulfonate (MMS, 3.67 mg/ml) were dissolved directly in 1 % DMSO in PBS. The concentrations to use were based on previous experiments in vitro and in ovo [5] , [6] , [7] . All solutions were freshly prepared before inoculation.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…It was also suggested that exposure to 50 mM gossypetin exhibits therapeutic effects against DNA damage at even a higher radiation dose exposure between 5 Gy and 20 Gy [55]. The aforementioned studies have demonstrated the anti-inflammatory and anti-oxidant properties of gossypetin in the management of radiation-induced oxidative stress (Figure 7) [55,70,72,73]. Taken together, gossypetin may alleviate oxidative-stress-induced diabetic complications due to its potent anti-oxidant and anti-inflammatory potential.…”
Section: Anti-oxidant and Anti-inflammatory Effects Of Gossypetinmentioning
confidence: 97%
“…In esophageal cancer cells, gossypetin promotes cell cycle arrest and apoptosis by increasing the expression of apoptotic markers such as BAX, cytochrome c, and caspases 83 . Gossypetin suppresses inflammation and promotes apoptosis in osteosarcoma cell lines by reducing the levels of proinflammatory cytokines and increasing the expression of apoptotic proteins 205 …”
Section: Role Of Selected Flavonols and Their Derivatives In Mitigati...mentioning
confidence: 99%